O resgate da identidade quilombola na escola municipal Professor Rildo Valadares, na comunidade de Jacundaí Moju-PA - SENA, Viviane Caroline Valadares (2019)
This paper aims to clarify the role of the school in the importance of fortification the quilombola identity of the students in the institution called the Rildo Valadares Municipal School of Elementary Education, located in the quilombola community of Jacundaí, in the municipality of Moju-PA. When talking about quilombola education, mainly referring to rural communities, a lot was proposed to define in an introductory way what quilombola education represents, as well as the ancestry and the territorial knowledge of the place where it is inserted. Therefore, it is necessary to fight for the importance of this form of education, understanding that its implementation is fundamental to the community school curriculum, through the combination of both ancestry and culture, because often the current curriculum is far from the historical and cultural reality of these students. This partnership between two knowledge (culture and ancestry) that completes and complements is in the territory as a new and very engaging form, explaining in a real and necessary way the existing reality and little shown of the quilombola territories. This analysis culminated in how this process of acceptability was and the reasons that preceded this inclusion of the knowledge of what would really be the implementation of the quilombola school curriculum in the school studied. It was also analyzed how such a curriculum helps in the formation and social interaction of the students of the quilombola community analyzed.